2015
DOI: 10.1172/jci82066
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic landscape of metastatic and recurrent head and neck squamous cell carcinoma

Abstract: BACKGROUND.Recurrence and/or metastasis occurs in more than half of patients with head and neck squamous cell carcinoma (HNSCC), and these events pose the greatest threats to long-term survival. We set out to identify genetic alterations that underlie recurrent/metastatic HNSCC. METHODS.Whole-exome sequencing (WES) was performed on genomic DNA extracted from fresh-frozen whole blood and patient-matched tumor pairs from 13 HNSCC patients with synchronous lymph node metastases and 10 patients with metachronous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 63 publications
4
96
0
Order By: Relevance
“…This observation from our two primary/recurrent tumour pairs (cases HKNPC001 and HKNPC012) seems to concur with our recent findings in primary/recurrent HNSCC. In paired primary/recurrent HNSCC samples, we also found that TP53 was the only shared annotated mutated cancer gene as defined by the Cancer Gene Census, COSMIC17. For these NPC patients, the recurrent or metastatic lesion appeared to show a single-nucleotide variant (SNV) clonality distribution different from that of the primary tumour, supportive of emerging new subclone(s) in recurrences.…”
Section: Resultsmentioning
confidence: 81%
“…This observation from our two primary/recurrent tumour pairs (cases HKNPC001 and HKNPC012) seems to concur with our recent findings in primary/recurrent HNSCC. In paired primary/recurrent HNSCC samples, we also found that TP53 was the only shared annotated mutated cancer gene as defined by the Cancer Gene Census, COSMIC17. For these NPC patients, the recurrent or metastatic lesion appeared to show a single-nucleotide variant (SNV) clonality distribution different from that of the primary tumour, supportive of emerging new subclone(s) in recurrences.…”
Section: Resultsmentioning
confidence: 81%
“…In 3 of 5 cases, we did not observe new mutations in the metastasis which could indicate that no new mutations are needed for survival and colonization. The latter is supported by a recent HNSCC study of nodal metastasis that shows a low degree of metastasis specific mutations [11]. However, low tumor content in patient 2, 4 and 5′s lymph node metastases lowers the resolution and ability to identify unique metastasis specific mutations by whole-exome sequencing in these patients.…”
Section: Discussionmentioning
confidence: 82%
“…More than 90% of tumors are head and neck squamous cell carcinomas (HNSCC). Recent studies suggest that they are very heterogeneous between patients [111]. Oral squamous cell carcinoma (OSCC), a subgroup of HNSCC, is primarily attributed to alcohol consumption and tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of IP 3 R3 is associated with aggressiveness of colorectal carcinoma since it is related with decreased 5-year survival. A mutation in IP 3 R3 encoding gene ITPR3 was identified in genetic landscape of metastatic and recurrent head and neck squamous cell carcinoma 27 . Similarly like IP 3 R1 and IP 3 R3, the dysregulation of IP 3 R2 was observed in chronic lymphocytic leukemia cells 28 .…”
Section: Altered Ca2+ Channels/transporters In Cancermentioning
confidence: 99%